Immunity of Inviolability in the Constitutions of the European Countries in the Process of Transition - Čiplić, Svetozar (Zbornik radova Pravnog fakulteta u Novom Sadu, 2013)
Enjoy immunity protects MPs from the influence of other authorities. This protection was determined according to the criminal liability of members. This immunity is immunity from liability in addition, Classical parliamentary privilege in democratic countries. All European countries in transition in the nineties of the last century have applied these immunities, but they themselves are further expanded.